The Playground of Public, Subsidized and Private Schools as a Space to Carry Out Bodily Practices: A Quasi-Ethnographic Study [el Patio de Las Escuelas Públicas, Subvencionadas y Privadas Como Espacio Para Realizar Prácticas Corporales: Un Estudio Cuasi Etnográfico] - Soto-Lagos, R (Federacion Espanola de Docentes de Educacion Fisica, 2023)
The World Health Organization (WHO) and the United Nations Educational, Scientific and Cultural Organization (UNESCO) have declared that physical inactivity is a problem that affects all the countries of the world and the strategic place to solve this problem are schools. The aim of this study was to understand how the school playground can become a space to develop body practices that can reduce physical inactivity. A qualitative study was made following a quasi-ethnographic study on one public, subsidized and private schools in Chile. The results indicate that school recess, Physical Education class and extracurricular activities are relevant moments which express similarities and differences between schools. The discussions propose that there are barriers and opportunities to inhabit the schoolyard. The conclusion express that the school playground is habited culturally and that both management teams, professionals and policy makers have an important role to collaborate in reducing physical inactivity at school. © Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF)